Isolation and Characterization of Ochrobactrum tritici for Penicillin V Potassium Degradation - Wang, Peng (mSphere, 2020)
Substantial concentrations of penicillin V potassium (PVK) have been found in livestock manure, soil, and wastewater effluents, which may pose potential threats to human health and contribute to the emergence of penicillin-resistant bacterial strains. In this study, bacterial strains capable of degrading PVK were isolated from sludge and characterized. Strain X-2 was selected for biodegradation of PVK. Based on morphological observations and 16S rRNA gene sequencing, strain X-2 was identified as an Ochrobactrum tritici strain. To enhance the PVK degradation ability of PVK, a whole-cell biodegradation process of Ochrobactrum tritici X-2 was established and optimized. In the whole-cell biodegradation process, the optimal temperature and pH were 30°C and 7.0, respectively. Under the optimized conditions, the degradation rate using 0.5 mg/ml PVK reached 100% within 3 h. During biodegradation, two major metabolites were detected: penicilloic acid and phenolic acid. The present study provides a novel method for the biodegradation of PVK using Ochrobactrum tritici strains, which represent promising candidates for the industrial biodegradation of PVK. IMPORTANCE Substantial concentrations of penicillin V potassium (PVK) have been found in the environment, which may pose potential threats to human health and contribute to the emergence of penicillin-resistant bacterial strains. In this study, antibiotic-degrading bacterial strains for PVK were isolated from sludge and characterized. Ochrobactrum tritici was selected for the biodegradation of PVK with high efficiency. To enhance its PVK degradation ability, a whole-cell biodegradation process was established and optimized using Ochrobactrum tritici. The degradation rate with 0.5 mg/ml PVK reached 100% within 3 h. The potential biodegradation pathway was also investigated. To the best of our knowledge, the present study provides new insights into the biodegradation of PVK using an Ochrobactrum tritici strain, a promising candidate strain for the industrial biodegradation of β-lactam antibiotics.